Oesophageal thermal protection during AF ablation: effect on left atrial myocardial ablation lesion formation and patient outcomes. (24th May 2021) - Leung, L; El Batran, A; Dhillon, G; Bajpai, A; Zuberi, Z; Li, A; Norman, M; Kaba, RA; Akhtar, Z; Evranos, B; Al Subaie, N; Sohal, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Dr Leung has received research support from Attune Medical (Chicago, IL). Dr Gallagher has received research funding from Attune Medical (Chicago, IL). Background: Randomized evidence has shown that controlled oesophageal cooling is effective at reducing oesophageal thermal injury during radiofrequency (RF) ablation for atrial fibrillation (AF) compared to standard care. The effect of oesophageal cooling on ablation lesion formation in left atrial myocardium and patient outcomes at 12-months had not been previously studied. Purpose: To determine the effect of oesophageal cooling on the formation of RF lesions, the ability to achieve procedural endpoints and long-term patient outcomes compared to standard care ablations. Methods: Ablation results and patient outcomes from a double-blind randomized controlled trial were analysed (IMPACT trial NCT03819946). AF ablation was guided by Ablation Index technology (30W at 350-400 AI posteriorly, 40W at 450 AI anteriorly). A blinded 1:1 randomization assigned patients to the use of an oesophageal temperature control device to keep oesophageal temperature at 4 degrees during ablation or standard practice using a single-sensor temperature probe. Ablation parameters and 12-month outcomes were analysed. Results:   We recruited 188 patients. Procedure and fluoroscopy times were similar. First pass pulmonary vein isolation and reconnection at the end of the waiting period were similar in both randomized groups (51/64 vs 51/68; p = 0.54 and 5/64 vs 7/68; p = 0.76, respectively). Posterior wall isolation was also similar: 24/33 vs 27/38; p = 0.88. Ablation effect on myocardial tissue, measured in impedance drop, was also similar: 8.6Ω (IQR: 6-11.8) vs 8.76Ω (IQR: 6-12.2; p = 0.25) and median catheter tip temperature was the same at 25.5 degrees. Arrhythmia recurrence was similar at 12 months (20.3% vs 26.8%, from 142 completed assessments; p = 0.66). Conclusions:   Oesophageal cooling has been shown to be effective in reducing ablation-related oesophageal thermal injury during RF ablation. Ablation data show that this protection does not make it any more difficult to achieve standard procedural endpoints or clinical success at 12-months.